Disruption of actin filaments in Zea mays by bisphenol A depends on their crosstalk with microtubules. (March 2018) - Stavropoulou, Konstantina; Adamakis, Ioannis-Dimosthenis S.; Panteris, Emmanuel; Arseni, Ermioni-Makedonia; Eleftheriou, Eleftherios P.
Abstract: Bisphenol A (BPA) is a widespread environmental pollutant, reportedly harmful to living organisms. In plant cells, BPA was shown to disrupt microtubule (MT) arrays and perturb mitosis, but its effects on filamentous actin (F-actin) have not been explored. Here we studied the effects of BPA on actin filaments (AFs) in meristematic root tip and leaf cells of Zea mays, by fluorescent labeling and confocal microscopy. Considering the typical dynamic interaction between MTs and AFs, the effects on these two essential components of the plant cytoskeleton were correlated. It was found that BPA disorganized rapidly AFs in a concentration- and time-dependent manner. The fine filaments were first to be affected, followed by the subcortical bundles, resulting in rod- and ring-like conformations. The observed differences in sensitivity between protodermal and cortex cells were attributed to the deeper location of the latter. Depolymerization or stabilization of MTs by relevant drugs (oryzalin, taxol) revealed that AF susceptibility to BPA depends on MT integrity. Developing leaves required harder and longer treatment to be affected by BPA. Ontogenesis of stomatal complexes was highly disturbed, arrangement of AFs and MT arrays was disordered and accuracy of cell division sequence was deranged or completely arrested. The effect of BPA confirmed that subsidiary cell mother cell polarization is not mediated by F-actin patch neither of preprophase band organization. On the overall, it is concluded that AFs in plant cells constitute a subcellular target of BPA and their disruption depends on their crosstalk with MTs. Graphical abstract: Highlights: Actin filaments constitute a subcellular target of bisphenol A in plant cells. Microtubule-actin "cross-talk" mediates the observed effects on actin. Ontogenesis of stomatal complexes is highly disturbed by bisphenol A.